2017
DOI: 10.1002/jcb.26432
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo effect of PD‐1/PD‐L1 blockade on microglia/macrophage activation and T cell subset balance in cryptococcal meningitis

Abstract: This study aimed to investigate the PD-1/ PD-L1 signaling pathway and its effects the activation of microglia/macrophage and balancing T cell subsets in cryptococcal meningitis (CM). A total of 126 CM patients and 126 healthy individuals were recruited for the study. The CM patients were treated with amphotericin B (AmB). Seventy five C57BL/6 mice were grouped into the normal control, CM model, CM + AmB, sham, and CM + PD-1 antibodies (Ab) groups. CD4 and CD8 T cells as well as microglia/macrophages were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Coincidentally, recent studies have shown that, PD-L1 expression in DCs induced by α-(1,3)-glucan from Aspergillus fumigatus through activating Wnt/β-catenin pathway promotes regulatory T-cell (Treg) polarization, suggesting that PD-L1 in DCs negatively regulates α-(1,3)-glucan-induced protective immune responses against A. fumigatus infection 43 , 44 . Moreover, it has been further reported that, PD-L1 expression in macrophages induced by Cryptococcus neoformans infection suppresses macrophage activation, and PD-L1 expression in T cells induced by C. albicans infection can promote T cell exhaustion 19 , 45 . It remains unclear whether PD-L1 expression in neutrophils induced by β-glucans can affect Treg polarization, macrophage activation or T cell exhaustion during C. albicans infection, which would be further explored in our future studies.…”
Section: Discussionmentioning
confidence: 98%
“…Coincidentally, recent studies have shown that, PD-L1 expression in DCs induced by α-(1,3)-glucan from Aspergillus fumigatus through activating Wnt/β-catenin pathway promotes regulatory T-cell (Treg) polarization, suggesting that PD-L1 in DCs negatively regulates α-(1,3)-glucan-induced protective immune responses against A. fumigatus infection 43 , 44 . Moreover, it has been further reported that, PD-L1 expression in macrophages induced by Cryptococcus neoformans infection suppresses macrophage activation, and PD-L1 expression in T cells induced by C. albicans infection can promote T cell exhaustion 19 , 45 . It remains unclear whether PD-L1 expression in neutrophils induced by β-glucans can affect Treg polarization, macrophage activation or T cell exhaustion during C. albicans infection, which would be further explored in our future studies.…”
Section: Discussionmentioning
confidence: 98%
“…e reduced activity of Rab5 inhibits TCR degradation and enhances TCR signaling pathways. In mouse 2 cells, knockdown of Rab5 selectively affects TCR downstream signaling and promotes the production of the corresponding cytokines [105]. It was reported that the number of CD4 + CD8 + thymocytes is obviously reduced in T-cell-specific Rab5-N133I transgenic mice, suggesting that Rab5 plays a key role in TCR transport and signal transduction [106].…”
Section: Rab5 and Antigen Recognitionmentioning
confidence: 99%
“…In mouse models of cryptococcosis, persistent lung infection sustains PD‐1 expression on dendritic cells and on macrophages 73 . Moreover, sustained PD‐1 expression on the macrophages on cryptococcosis brain mouse models promotes fungal growth through upregulated proliferation of Cryptococcus ‐infected macrophages, facilitating fungal dissemination 73,78 . The PD‐1 upregulation further increases activation of microglial cells and promotes Th2 cellular‐activated responses while downregulating Th1‐activated responses 78 .…”
Section: Pd‐1 Expression On Lung Immunocytesmentioning
confidence: 99%
“…73 Moreover, sustained PD-1 expression on the macrophages on cryptococcosis brain mouse models promotes fungal growth through upregulated proliferation of Cryptococcus-infected macrophages, facilitating fungal dissemination. 73,78 The PD-1 upregulation further increases activation of microglial cells and promotes Th2 cellular-activated responses while downregulating Th1-activated responses. 78 Of note, application of anti-PD-1/PD-L1 antagonists (PD-1 blocking antibodies) altered PD-1-modulated responses by promoting fungal clearance, upregulating ICOS and XO40 on Th1, Th2, Th17 and regulatory T cells while downregulating IL-5 and IL-10 immune regulatory cytokines in the model of cryptococcosis.…”
Section: Pd -1 E Xpre Ss I On On Lung Immunoc Y Te Smentioning
confidence: 99%
See 1 more Smart Citation